IT Industry and Business Oppurtunities - R H Sayyidah; Tatik Fidowaty (Peneliti.net, 2021)
The purpose of this study is to find out the influence of Kpop (Korean Pop) had to create new business opportunities by utilizing available social media in Indonesia. The research used descriptive method by describing, explaining, and validating social phenomena through the distribution of online questionnaires based on existing data. Judging from the 58 data obtained, as many as 84.5% stated that business in the Kpop field could be seen as a promising business opportunity. This data was obtained from two types of respondents, namely Kpop fans and non-Kpop fans. This opportunity must be utilized as well as possibly one of the sources of funds for our businesses.